Effect of fertility levels on sesame (Sesamum indicum) varieties under agri-horti system - PATEL, ABIB KUMAR; BOHRA, J S; DEWANGAN, SAVITA; SINGH, ALOK KUMAR (The Indian Journal of Agricultural Sciences, 2022)
The move towards higher production of quality crops with alternative land use systems i.e. agri-horticulture system in combination with adequate supply of nitrogen, phosphorus, potassium and sulphur and improved varietal selection can solve the problem of lower productivity. Consequently, the present study illustrated that selection of crop varieties according to land use system with balanced nutrients supply can optimize the crop production in sustainable manner. The study showed that the performance of crop with different varietal selection was influenced by the different levels of nutrients supply. The growth and yield parameters were significantly affected with the application of 60, 30, 30, 30 kg of N, P2O5, K2O and S/ha and produced significantly higher seed yield (675 kg/ha) as compared to 40, 20, 20, 20 kg of N, P2O5, K2O and S/ ha and 20, 10, 10, 10 kg of N, P2O5, K2O, and S/ha among various fertility levels.